Functional Reconstruction of Large Medial Canthal Defects - Parker, Adam M.; Richardson, Matthew A.; Jordan, J. Randall (Facial Plastic Surgery, 2014)
The aim of this study is to describe a surgical technique for the reconstruction of large medial canthal defects involving the lacrimal apparatus following excision of medial canthal tumors. Many different techniques for constructing a neopassage from the lacrimal sac to the nasal sinuses have been investigated and described in the literature. However, there continues to be difficulty with successful functional reconstruction of the lacrimal outflow tract without the long-term use of an indwelling tube. We herein describe a technique utilizing a paramedian forehead flap combined with AlloDerm (LifeCell Corporation, Township of Branchburg, NJ) as the conduit for reconstruction of the medial canthus and lacrimal outflow tract. We present a case series of three patients successfully reconstructed with the above technique and describe their presentation, treatment, and postoperative course. We provide a detailed description of the surgical technique and document the success of the technique in regard to patency and postprocedure function of the lacrimal conduit.
Keywords: medial canthal defect; lacrimal apparatus; epiphora; paramedian forehead flap; AlloDerm